1981
DOI: 10.1055/s-0038-1650182
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Raynaud's Syndrome with Prostacyclin

Abstract: SummaryThere is evidence to suggest that platelet activation occurs in Raynaud’s syndrome. We evaluated the effect of prostacyclin (PGI2) a potent antiplatelet and vasodilator agent in 5 female patients with Raynaud’s syndrome. Outpatient visits were made at weekly intervals for 4 weeks. At the first visit buffer solution (Wellcome Laboratories) was infused intravenously for 5 hrs, thereafter three five hr infusions of PGI2 at a peak dose of 10 ng/ Kg/min were given. Six weeks after the infusions patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…One explanation of this could be that the prostaglandin endoperoxides normally required to form TXA2 are diverted initially to the formation of vasoconstrictor prostaglandins rather than the vasodilator prostaglandin, PGI2. PGI2 has been shown to increase hand temperatures when given in therapeutic doses (Belch et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…One explanation of this could be that the prostaglandin endoperoxides normally required to form TXA2 are diverted initially to the formation of vasoconstrictor prostaglandins rather than the vasodilator prostaglandin, PGI2. PGI2 has been shown to increase hand temperatures when given in therapeutic doses (Belch et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, PGI2 and its analogue had beneficial effects on various experimental thrombosis and occlusive dis eases (14,38,39). Moreover, PGI2 has clinically been used to prevent the thrombus formation in the extracor poreal circulation (40,41) and the arterial diseases such as Burger (42) and Raynaud's disease (43,44).…”
Section: Effects On Extracorporeal Circulationmentioning
confidence: 99%
“…Pain relief was a striking feature, presumably associated with the increased blood flow as indicated by increased temperature of the hands and fingers (142). Belch and co-workers (143) have also reported successful treatment in 4 out of 5 patients and a double-blind clinical trial (144) has now confirmed these results in Raynaud's phenomenon. There was an overall improvement still present at 6 weeks in 6 of 7 patients receiving prostacyclin, but only in 1 of 7 receiving placebo.…”
Section: (D) Prostacyclin and Atherosclerosismentioning
confidence: 90%